Analisis Variasi Proses Bisnis Manufaktur Dengan Menerapkan Process Mining (Studi Kasus: PT Kimia Farma, Tbk) - Annisa Arifa Sesyazhade; Nanang Yudi Setiawan; Ismiarta Aknuranda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
PT Kimia Farma Tbk, or Kimia Farma is the first company in Indonesia that focus on pharmacy industry and was built on 1817. As the company that has been taking role for a long time, Kimia Farma has their own strict Standard Operational Procedure (SOP) for their manufacture processes. Analysis on the manufacture process, especially related to the variations that have potential to occur in a process is needed to get the optimal performance. The manufacture processes that analyzed in this study are capsule, cream, syrup, and tablet. The first step is to model and simulate the processes one by one based on the SOP using YAWL tools. In parallel, the other first step is to transform the event log from the ERP system using Disco tools. The analysis is applied using process mining method in ProM tools. The goals are to analyze the variant activity that occur in the process and to classify them into restriction or extension. The result shows that the processes of capsule and syrup are not showing any variability in their manufacture process, this finding is proven by the fitness score that reach 1 for each process.. On the other hand, the result shows that tube blowing activity in cream manufacture process is a variability because of its uncertain position, this finding is proven by the fitness score that only reach 0.93 and this variation is also classified as variability by restriction. And the result also indentified that there is a variation that happen in activity In Process Control (IPC) from tablet manufacture process because of its looping activity, this finding is proven by the fitness score that only reach 0.99, and this variation is also classified as a variability by extension.